DAMPAK PEMBANGUNAN RUAS JALAN AMPERA – GANTI TERHADAP PENDAPATAN MASYARAKAT DI KELURAHAN GANTI KECAMATAN BANAWA KABUPATEN DONGGALA - Nurhasna, Nurhasna (Katalogis, 2014)
Construction  of  transportation  infrastructure  have  a  close  relationship  with  the  level  ofeconomic activities. This study aims to clarify the effect of the construction of Roads Ampera - Ganti to the socio-economic Change in the Village, District Banawa, Donggala, particularly in terms of income levels, consumption patterns and ownership of assets. The method used is the method of survey research instrument was a questionnaire distributed to 91 respondents who live in Ampera - Ganti  Roads. To get the amount of income and expenditure before and after the construction of Roads Ampera - Ganti, then the data were analyzed by cross-tabulation method and the hypothesis was tested by paired sample t-test. Furthermore, to determine the extent to which the relationship between the increase in income and consumption patterns of ownership of the assets of the analysis used Product-Moment Correlation Coefficient (PMCC) or (Pearson's r) of Karl Pearson. The results showed that after 2 years of establishment Roads Ampera - Ganti, an increase in people's income by 35.21% and the level of public expenditure also rose by 27.11%. The increase in revenue is also affected patterns of consumption and asset ownership but not significantly, even the relationship between the two variables based on the results of testing found low correlation coefficient value, ie respectively 0.323 and 0.255.